2021
DOI: 10.3389/fdgth.2021.753115
|View full text |Cite
|
Sign up to set email alerts
|

Staying Active While Staying Home: The Use of Physical Activity Technologies During Life Disruptions

Abstract: One impact of the Covid-19 lockdowns was a restriction on people's ability to engage in physical activity in previously routine ways. This paper presents a two-stage mixed-method study exploring how people used technology to stay physically active during this period. We found that activity trackers reminded people to be active, while virtual coaching (i.e., video tutorials and online classes) helped them stay connected. The lockdown increased people's awareness of their activity levels and removed barriers to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 50 publications
2
5
0
Order By: Relevance
“…The results of our study showed that both gold and silver athletes were more motivated to use live streaming than they were to use the pre-recorded training modality. This finding is in accordance with the research of Newbold et al [ 23 ], who showed that live-streaming classes offered a way to stay connected with people during the lockdown and to continue with exercise classes they would previously have attended in person, providing a sense of community. These results are in line with a study by Bonavolontà et al [ 38 ] on the level of enjoyment of home-based training for 140 children and adolescents from 23 different Apulian Tennis Clubs, which showed that those who received online support and guidance from their instructors showed significantly higher average enjoyment levels than the group who had no such indication.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of our study showed that both gold and silver athletes were more motivated to use live streaming than they were to use the pre-recorded training modality. This finding is in accordance with the research of Newbold et al [ 23 ], who showed that live-streaming classes offered a way to stay connected with people during the lockdown and to continue with exercise classes they would previously have attended in person, providing a sense of community. These results are in line with a study by Bonavolontà et al [ 38 ] on the level of enjoyment of home-based training for 140 children and adolescents from 23 different Apulian Tennis Clubs, which showed that those who received online support and guidance from their instructors showed significantly higher average enjoyment levels than the group who had no such indication.…”
Section: Discussionsupporting
confidence: 92%
“…Many forms of online training were used during the COVID-19 home confinement period [ 4 , 14 , 15 , 23 ]. To our knowledge, this is the first study aimed at investigating the differences between the live-streamed and pre-recorded online training modalities for RG athletes and coaches of different technical levels during the first COVID-19 national lockdown in Italy.…”
Section: Discussionmentioning
confidence: 99%
“…It was not as good as being there, but at least we did something so that we wouldn't be sedentary for too long." P3 These findings align with Newbold et al [54], who argue that the emergence of online physical exercise programs and recorded classes facilitated physical exercise routines despite lockdowns, social isolation, and gym closures.…”
Section: Resultssupporting
confidence: 78%
“…One of the most important and easy ways to gain healthy habits and keep all the body's systems, but perhaps the most important one, the immune system, is to exercise. In addition, considering these effects in the post-pandemic period, it is thought that online methods can continue to be used [ 3 , 4 ]. Another exercise method used as tele-exercise in the literature is Pilates [ 5 ].…”
Section: Introductionmentioning
confidence: 99%